Tinjauan Peran Pemerintah dalam Penyediaan Barang dan Jasa Publik di Indonesia : Penelitian - Sri Rosni Alfiat Laia; Aqilah Apritia Parawanza; Sarah Desnita Manihuruk; Jenaya Febina; Yolanda Tampubolon (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The provision of public goods and services is a primary function of government in a modern economic system due to their nature, which cannot be optimally provided by market mechanisms. Public goods have the characteristics of non-rivalry and non-excludability, which give rise to market failures and require state intervention to ensure equitable provision. This study aims to provide a comprehensive overview of the government's role in the provision of public goods and services in Indonesia, with a focus on the theoretical basis, forms of government intervention, and implementation challenges in strategic sectors such as education, health, security, and infrastructure. The research method uses a library research approach through analysis of academic literature, scientific journals, official government reports, and public economics textbooks. The analysis is conducted descriptively and qualitatively to integrate theoretical concepts with policy practices in Indonesia. The results of the study indicate that the Indonesian government plays a role as a direct provider, regulator, and facilitator of cooperation in the provision of public goods. Although government policies have improved access to and the quality of public services, challenges such as inter-regional disparities, budget constraints, and governance issues continue to limit the effectiveness of public goods provision. This study emphasizes the importance of strengthening fiscal capacity, improving spending quality, transparency, and policy innovation as strategies to optimize the government's allocation function in supporting inclusive and sustainable development.